Efficacy of prehospital National Early Warning Score to predict outpatient disposition at an emergency department of a Japanese tertiary hospital: a retrospective study. Issue 6 (15th June 2020) - Endo, Takuro; Yoshida, Toru; Shinozaki, Tomohiro; Motohashi, Takako; Hsu, Hsiang-Chin; Fukuda, Shunsuke; Tsukuda, Jumpei; Naito, Takaki; Morisawa, Kenichiro; Shimozawa, Nobuhiko; Taira, Yasuhiko; Fujitani, Shigeki
Abstract : Objectives: The National Early Warning Score (NEWS) was originally developed to assess hospitalised patients in the UK. We examined whether the NEWS could be applied to patients transported by ambulance in Japan. Design: This retrospective study assessed patients and calculated the NEWS from paramedic records. Emergency department (ED) disposition data were categorised into the following groups: discharged from the ED, admitted to the ward, admitted to the intensive care unit (ICU) or died in the ED. The predictive performance of NEWS for patient disposition was assessed using receiver operating characteristic curve analysis. Patient dispositions were compared among NEWS-based categories after adjusting for age, sex and presence of traumatic injury. Setting: A tertiary hospital in Japan. Participants: Overall, 2847 patients transported by ambulance between April 2017 and March 2018 were included. Results: The mean (±SD) NEWS differed significantly among patients discharged from the ED (n=1330, 3.7±2.9), admitted to the ward (n=1263, 60.3±3.8), admitted to the ICU (n=232, 9.4±4.0) and died in the ED (n=22, 110.7±2.9) (p<0.001). The prehospital NEWS C-statistics (95% CI) for admission to the ward, admission to the ICU or death in the ED; admission to the ICU or death in the ED; and death in the ED were 0.73 (0.72–0.75), 0.81 (0.78–0.83) and 0.90 (0.87–0.93), respectively. After adjusting for age, sex and trauma, the OR (95% CI) of admission to the ICU or death in the ED for the high-risk (NEWS ≥7) and medium-risk (NEWS 5–6) categories was 13.8 (8.9–21.6) and 4.2 (2.5–7.1), respectively. Conclusion: The findings from this Japanese tertiary hospital setting showed that prehospital NEWS could be used to identify patients at a risk of adverse outcomes. NEWS stratification was strongly correlated with patient disposition.